Association of Borna disease virus with autism spectrum disorder in Turkish children - Altunçekiç Yıldırım, Arzu; Çetinkol, Yeliz; Esnafoglu, Erman; Çalgın, Mustafa Kerem (Journal of Surgery and Medicine, 2020)
Aim: Autism spectrum disorders are lifelong neurodevelopmental disorders whose pathogeneses are not fully understood. Borna disease virus is a neurotropic virus that affects the central nervous system. Considering the neuropsychiatric and behavioral effects of the virus, it can be suggested that it may play a role in autism spectrum disorder. However, there are insufficient evidence to support this. In this study, we aimed to investigate the presence of Borna disease virus in patients with autism spectrum disorders and healthy controls. Methods: This case-control study, performed in children with autism spectrum disorders and a control group, included patients with autism who visited the Child and Adolescent Psychiatry outpatient clinic between December 2017 - December 2018. Borna virus positivity was assayed with the ELISA method in serum samples. Data was analyzed using SPSS version 22. Results: The study included 63 children diagnosed with autism spectrum disorder and 31 healthy controls. The age range of autism patients was 3-14 years, their mean age was 7.83 (1.96) years, and The Childhood Autism Rating Scale score was 51.09 (5.71). The seropositivity rate for Borna disease virus in the autism and healthy control groups were 25.39% and 25.80%, respectively (P=0.966). For all patients, seropositivity rate was 25.53%. Conclusion: No relationship was found between autism spectrum disorders and Borna disease virus. The clinical significance of Borna disease virus positivity in society is unknown. We conclude that Borna disease virus is not involved in the pathogenesis of autism spectrum disorders.